Implementation of Electronic Applications of The Directorate General Treasure - A, M. Awaluddin; Santos, Hezron Alhim Dos; Rahman, Sugirah Nour; Irmawati, Irmawati (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aims to analyze implementation, supporting factors, innovation, as well as the strengths and weaknesses of implementing the Directorate General of Treasury's electronic application. This study used descriptive qualitative method. The results of the study show that the e-office services provided by the Makassar II State Treasury Office are divided into six types of work unit application categories available on the Makassar Directorate General of Treasury website, namely GPP applications, VAT applications, POK applications, SAS applications, SIMAK applications, and SAIBA applications. Supporting factors that influence the implementation of e-office at the Makassar II State Treasury Office are telecommunications infrastructure, internet connection, human resources, availability of funds, and legal instruments. The innovation carried out by the Makassar II State Treasury Office to improve e-office services is by developing Warkopta and Tudang Sipulung services. The advantage of using e-office in an agency is that it can carry out administrative activities more easily, quickly, transparently, orderly, integrated, productive, accurate, safe, and efficient. The disadvantage of using e-office in an agency is that it is vulnerable to data leaks because all activities including personal identity are contained in the system.